PERBANDINGAN MOTIVASI BELAJAR PESERTA DIDIK BERASAL DARI PULAU DURAI DAN LUAR PULAU DURAI DI SMA NEGERI 1 DURAI - Lieona Lieona; Gimin Gimin; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The research was conducted with the aim to determine the level of participant motivation students come from Durai isaland. The motivation of students outside Durai island and to know the level of differences in learning motivation of students who come from Durai island with students outside Durai island. With conditions the students must cross the sea using pompon (small boats) and also the didtance taken 30 minutes from the port village to school with distance of 10 minutes. Therefore the writer wants to see whether the distance and the difference in the living environment can influence the level of learning motivation of Durai island student and outside Durai island. The research was was conducted at SMA N 1 Durai Jl. Sersan Ibrahim Ya’kop Durai, Karimun Kepri. The population in this study amounted to 172 people. The sampel in this study amounted to 63 people namely Durai island 49 people and outside Durai island 14 people sampling using Proportionate stratified random sampling technique. This technique is used the population has a member or element that is not and proportionally distributed. Technique of daa collection is observation, interview, questionnaire and documentation. This research method uses quantitative descriptive tchnik descriptive data analysis percentage and differen test two separate samples using each of them then using motorbike (Honda) and homogeneous SPSS version 21. The results show that the answer is that the motivation level of Durai island student is very this higt is proven to be as much as 79% in the range of 75,01% - 100% while the motivation of pesetas students outside Durai island is 88% in the range of 75,01 % - 100%. And the ull results are based on SPSS version 21 that there is no difference in motivation of Durai island students and outside Durai island. As evidenced by sig> 5% ( 0,83>0.5) and t count 1,763 smaller than T tabel 1.99834Keywords: comparison, learning motivation